Tinjauan Yuridis Perizinan dalam Pengelolaan Lingkungan Hidup Sebagai Sarana Pencegahan Pencemaran dan Kerusakan Lingkungan Hidup - Haryono, Haryono; Anggraini, Sri; Iswahyudi, Gesang (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Environmental problems are not national problems but are also global problems, this is because the scope of environmental pollution that occurs is no longer limited to one particular area but can extend to other regions or other countries and this affects the condition of world ecosystems such as the case of protected forest fires. in Sumatra and Kalimantan, where the smoke crosses Indonesia to reach Singapore and Malaysia and has an impact other than air pollution due to smoke but also global warming due to the reduced forest area that supports the world's ecosystems. In Indonesia, many cases of environmental pollution have not been handled optimally. This is reflected in the description of the community in utilizing nature, such as the method used to open agricultural land and plantations, how to catch fish, how to dispose of garbage, as well as other activities that have an impact on pollution and or damage to the environment. This writing uses 2 (two) approach methods, namely: Statute approach, which is an approach that seeks answers to existing problems through the relevant laws and regulations. Conceptual approach is an approach that seeks answers to the formulation of the problem. through legal materials related to licensing.